Innovation in SMEs and financing mix - Joanna Błach; Monika Wieczorek-Kosmala; Joanna Trzęsiok (Journal of Risk and Financial Management, 2020)
This study addresses the types of innovation activity of SMEs (Small and medium-sized enterprises) in the European Union and its association with financing decisions. The main objective is to capture the cross-country differences in the types of innovation in SMEs and then investigate the relationship between the types of innovations and relevance of a given type of funding. In the empirical examinations, we use the non-parametric methods, due to the nature of the data. We have found out that there are differences in the types of innovation activity of SMEs in the cross-country dimension. We have also confirmed the contingencies between the types of innovations undertaken by SMEs in each cluster of the European countries, which suggests that various types of innovations co-exist. However, we have not found any unified pattern of correlations between the relevance of a given source of financing and a given type of innovation. Our study contributes to the ongoing debate on the different intensity of innovation activity of SMEs, as linked to the problem of the SMEs financing gap as one of the fundamental drivers of innovation.
Keywords: 330; innovation; capital structure decisions; financing gap; innovative activity; SMEs financing